Analisis Yuridis Hak Dan Kewajiban Para Pihak Dalam Hubungan Kerja Serta Pemutusan Hubungan Kerja Pada Perusahaan Start-UP - Mariana, Lena Agustina (Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid growth of the start-up industry in Indonesia introduces new challenges in labor practices, particularly concerning flexible contracts and employment termination. The non-hierarchical structures and dynamic work patterns often clash with existing labor regulations. Many workers face job insecurity, neglect of basic rights such as fair wages, social security, and leave, and even unilateral termination without adequate compensation. This study analyzes how Law Number 13 of 2003 and Government Regulation Number 35 of 2021 regulate the rights and obligations of parties in employment relations, especially in the start-up sector. It also explores the legal challenges in enforcing labor protections amidst trends of flexible contracts and outsourcing systems. A descriptive juridical approach is used to evaluate the effectiveness of legal protections offered to workers in increasingly flexible and disruptive work environments.